A coaxial triboelectric nanogenerator fiber for energy harvesting and sensing under deformation. Issue 13 (15th March 2017) - Yu, Xinghai; Pan, Jian; Zhang, Jing; Sun, Hao; He, Sisi; Qiu, Longbin; Lou, Huiqing; Sun, Xuemei; Peng, Huisheng
Abstract : A coaxial triboelectric nanogenerator fiber for both energy harvesting and sensing was developed by using aligned carbon nanotube sheets. Abstract : A novel coaxial triboelectric nanogenerator fiber for both energy harvesting and sensing under deformation was developed by using aligned carbon nanotube sheets as inner and outer electrodes and designing porous structures in triboelectric polymers of polydimethylsiloxane and polymethyl methacrylate. The fiber device was flexible, stretchable, weavable and adaptable for integration with various other electronic devices. Besides the capability of converting multidirectional mechanical energies to electricity with a high durability, it can also sense diverse mechanical stimuli such as pressing, bending, twisting, stretching and vibrating.